2016
DOI: 10.1002/2015jg003163
|View full text |Cite
|
Sign up to set email alerts
|

Evolution to decay of upwelling and associated biogeochemistry over the southeastern Arabian Sea shelf

Abstract: Observations along 10 shelf transects in 2012 near 10°N in the southeastern Arabian Sea revealed the usual warm oligotrophic conditions during the winter monsoon and upwelling of oxygen-deficient, nutrient-rich cool water during the summer monsoon (SM). By changing an oligotrophic to a nutrient-replete condition, the upwelling is the major process that regulates the biogeochemistry of this shelf. Its onset is perceptible at 100 m depth between January and March. The upwelling reaches the surface layer in May a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 144 publications
(90 citation statements)
references
References 39 publications
8
79
0
Order By: Relevance
“…The oxygen concentration on the shelf is expected to be lower than that offshore because of a higher oxygen consumption on the shelf, particularly associated with the sediment respiration process, which in our model is a very simple representation. Despite lower oxygen content on the shelf, there is a very good phase agreement between the oxygen seasonal variations from CaTS in situ measurements and the corresponding offshore variations derived from the WOA and model, suggesting a strong offshore-shelf connection through dynamical upwelling process, as suggested by Banse (1959), Carruthers et al (1959), and Gupta et al (2016).…”
Section: Physical Control Of the Seasonal Oxygen Variability Off The Wcimentioning
confidence: 67%
See 4 more Smart Citations
“…The oxygen concentration on the shelf is expected to be lower than that offshore because of a higher oxygen consumption on the shelf, particularly associated with the sediment respiration process, which in our model is a very simple representation. Despite lower oxygen content on the shelf, there is a very good phase agreement between the oxygen seasonal variations from CaTS in situ measurements and the corresponding offshore variations derived from the WOA and model, suggesting a strong offshore-shelf connection through dynamical upwelling process, as suggested by Banse (1959), Carruthers et al (1959), and Gupta et al (2016).…”
Section: Physical Control Of the Seasonal Oxygen Variability Off The Wcimentioning
confidence: 67%
“…Neutral or negative IOD years are, however, not necessarily anoxic, indicating that a neutral or negative IOD is a necessary but not a sufficient condition for severe anoxia. A recent study by Gupta et al (2016) revealed that the oxygen deficiency in 1959 along the WCI was more severe than in 2012, a conclusion consistent with the occurrence of a negative IOD in 1959 and a positive one in 2012. Similarly, in situ measurements also revealed that subsurface oxygen concentrations were significantly lower at the turn of the 20th century than in the 70s ): our simulation exhibits a similar behavior (see Fig.…”
Section: Influence Of the Iod On The Interannual Oxygen Variability Amentioning
confidence: 69%
See 3 more Smart Citations